Stereotype Gender Pada Mahasiswa Universitas Negeri Padang Tahun 2019-2021 - Tiara Rahayu; Fatmariza Fatmariza; Al Rafni; Henni Muchtar (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study aims to reveal gender stereotypes among college students. The focus of this research is on the indicators of the form, causes, and impact of gender stereotypes. This study used a descriptive quantitative method, with a stratified random sampling technique. Respondents in this study were 75 respondents. The results of this study indicate that as many as 38.67% of students do not have gender stereotypes, even so there are still students who have gender stereotypes as much as 29.33%. Based on the results of the study, it can be concluded that the understanding of gender stereotypes among students needs to be further improved so that gender justice and equality can be realized.